Relations between Interlukin-6 and Some Biochemical Parameters in Diabetic Foot Syndrome (Medico Legal Update, 2021)
The aim of this study is to predict the incidence of diabetic foot syndrome in type 2 diabetic patients bymeasuring some parameters (IL-6, FBS, MDA, CP, BMI). Samples were obtained from (75) type II diabeticpatients with and without diabetic complications (diabetic foot and diabetic neuropathy), as well as (25)healthy controls as a control group. They were divided into four groups: Group A (the control group):-It included (25) healthy individuals aged between (35-70 years). Group B (Diabetics type II withoutcomplications):- Includes (25) patients, their ages range (35-70 years). Group C (diabetic patients withdiabetic neuropathy):- It included (25) patients whose ages ranged from (35-70 years). Group D (diabeticpatients with diabetic foot syndrome): - Included (25) patients whose ages ranged from (35-70 years). Theresults showed a significant increase in the levels of (IL-6, FBS, MDA, CP) in all groups of type II diabetespatients with and without complications compared to the control group (P? 0.05). There was a significantincrease in the parameters measured in the group of diabetic patients with type II diabetic foot syndrome(DF) compared to the group of diabetic patients with type II disease Diabetic neuropathy (DN), and theresults also showed a significant increase in group DN compared to group of type II diabetic patients (DM)(P? 0.05). Our study show Interleukin-6 values, as well as oxidative stress, could predict the future incidenceof diabetic foot syndrome.